Kajian Hadits: Ilmu-ilmu yang terkait dengan Matan Hadits - Samsul Hidayat; Miftahul Umam (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2023)
Technological developments can have both positive and negative impacts. This makes it easier for Muslims to spread their da'wah, but on the other hand the information that is spread often exceeds the limit. So that every phenomenon in society that smells of religion is associated in a hadith. So we need a science of hadith (matan hadith) to be able to guarantee the truth of the hadith. As for the results of this study, the validity of the hadith can be known through 1) the science of matan in terms of issuing menstruation (shahih al-kalam): Hadith Qudsi is one of them. 2) Sciences to explain matan: Gharib al-Hadis, Asbab al-Wurud al-Hadis, Naskh Mansukh Hadith, Differences of Hadith and Muhkam al-Hadis and others.